Arid grassland bee communities: associated environmental variables and responses to restoration. (5th December 2019) - Smith DiCarlo, Lauren A.; DeBano, Sandra J.; Burrows, Skyler
Abstract : In recent years restoration project efforts in arid grasslands of the Pacific Northwest have increased; however, little is known about the bee communities in these areas or how restoration affects them. Native bees provide an essential ecosystem service through pollination of crops and native plants and understanding their response to restoration is a high priority. To address this issue, we conducted a three‐year study in an arid bunchgrass prairie with three objectives: (1) describe the bee community of this unique grassland type and its temporal variability; (2) investigate environmental variables influencing the community; and (3) examine effects of restoration on the community. We identified 62 bee species and found strong seasonal and inter‐annual variation in bee abundance, richness, diversity, and species composition. Unexpectedly, these temporal trends did not correspond with patterns in floral resources; however, several variables were associated with variation in bee abundance, richness, and diversity among sites. Sites with high levels of litter cover had more bees, while sites with taller vegetation or more blooming flowers had greater species richness but lower diversity. We found no detectable effect of restoration on bee abundance, richness, diversity, or composition. Species composition at native sites differed from those in actively and passively restored sites, which did not differ from each other. Restored sites also had fewer flowers and differing floral composition relative to native sites. These results suggest that if grassland restoration is to benefit bees, efforts should focus on both expanding floral resources and enhancing variables that influence nesting habitat.